Prevent Osteoporosis: Catch the Silent Thief - Linda B. Bobroff (EDIS)
Osteoporosis means porous bones, or bones that have so many openings (pores) that they can easily break or be crushed. In the United States, 54 million people either have osteoporosis (10 million) or are at high risk (44 million) because they have low bone mass. By 2020, one in two Americans over the age of 50 is expected to have osteoporosis of the hip or be at high risk of developing the condition. This 11-page fact sheet discusses risk factors, calcium for bone building, calcium-rich foods, calcium supplements, vitamin D, and exercise. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, revised February 2017.